Labile iron derived from autophagy-mediated ferritin degradation in cardiomyocytes under pressure overload increases myocardial oxidative stress and develops heart failure in mice. (14th October 2021) - Omiya, S; Ito, J; Otsu, K
Abstract: Introduction: Heart failure is the leading cause of morbidity and mortality in developed countries, and abnormal iron metabolism is common in patients with heart failure. While iron is essential for metabolic homeostasis, it can increase oxidative stress, such as lipid peroxidation resulting from the generation of harmful reactive hydroxyl radicals through the Fenton reaction. Iron is stored in ferritin, which consists of ferritin heavy (FTH1) and light chains. FTH1 has ferroxidase activity and sequestrates labile ferrous iron. Its protein expression is mediated through nuclear receptor coactivator 4 (NCOA4)-mediated autophagic degradation, known as ferritinophagy. However, the role of ferritinophagy in the stressed heart remains unclear. Methods: Cardiomyocyte-specific NCOA4-deficient (KO) mice were generated and subjected to pressure overload by transverse aortic constriction to induce heart failure. Cardiac remodelling was assessed by echocardiography and histological and molecular analyses four weeks after the operation. Furthermore, lipid peroxidation was inhibited by its potent inhibitor, ferrostatin-1. Results: Deletion of NCOA4 in mouse hearts did not affect cardiac phenotypes and FTH1 protein level at baseline but improved cardiac systolic function (Fractional shortening, control littermates 21.9% vs KO 45.9%) accompanied by the attenuation of ferritin degradation (The protein level of FTH1, controls 42.9% vs. KO 67.2% of sham-operated hearts) 4 weeks after pressure overload compared to the control littermates. The number of LC3B (a marker of an autophagosome)- and FTH1-positive dots (controls 2.64/10 3 μm 2 vs KO 0.30/10 3 μm 2 ) and that of LAMP2a (a marker of a lysosome)- and FTH1-positive dots (controls 3.68/10 3 μm 2 vs KO 1.77/10 3 μm 2 ) increased in TAC-operated control hearts, which was attenuated in TAC-operated NCOA4-deficient hearts. The ratio of ferrous iron to the FTH1 protein level, which represents the non-binding fraction of labile ferrous iron to FTH1, was higher in TAC-operated control hearts than in the sham-operated controls and TAC-operated NCOA4–deficient hearts. Although pressure overload increased the level of malondialdehyde, a marker for lipid peroxidation in control hearts, its level was reduced by deletion of NCOA4 (controls 1.12 nmol/mg vs KO 0.68 nmol/mg). Ferrostatin-1 significantly mitigated the development of pressure overload-induced dilated cardiomyopathy in wild-type mice (Fractional shortening, saline 21.4% vs ferrostatin-1 41.7%). Conclusions: Pressure overload-induced ferritinophagy in cardiomyocytes increases myocardial labile iron pool and oxidative stress resulting in the development of heart failure in mice. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British heart foundation